Luminescence of Ca2LiSiO4F: Ce3+, Tb 3+ phosphors - Huang, L.; Guo, M.; Zhao, S.; Deng, D.; Wang, H.; Hua, Y.; Jia, Guohua; Xu, S. (2013)
Ce3+, Tb3+ singly-doped and co-doped Ca 2LiSiO4F phosphors have been synthesized through conventional solid-state reaction. Their luminescence properties are studied. Under UV excitation, Ce3+ singly-doped Ca2LiSiO 4F phosphor emit blue light (460 nm), while Tb3+ singly-doped phosphor presents yellowish green color with emission peaks at 414, 437, 486, 543, 588, and 620 nm. The excitation spectra of Ce3+ and Tb3+ co-doped Ca2LiSiO4F monitored at 543 nm show a strong broad excitation band in the UV region with a maximum at 362 nm. Excited at 370 nm, Ce3+ and Tb3+ co-doped Ca 2LiSiO4F phosphor presents bluish white color with the emission peaks at 460, 486, 543, 588, and 620 nm. The energy transfer from Ce3+ to Tb3+ occurs in the co-doped Ca 2LiSiO4F phosphors and is a resonance-type energy transfer due to the spectral overlap between the 460 nm emission of Ce3+ and the excitation spectra monitored at 543 nm of Tb3+. The decay curves of 460 emission from Ce3+ in the co-doped phosphors and the calculated lifetime results confirm the energy transfer. The results indicate that these phosphors have potential as phosphor candidates used for white LEDs pumped by UV chips. © 2012 The Electrochemical Society.